2018
DOI: 10.1007/s00018-018-2838-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxisome proliferator-activated receptors in non-alcoholic fatty liver disease inflammation

Abstract: Overweight and obesity have been identified as the most important risk factors for many diseases, including cardiovascular disease, type 2 diabetes and lipid disorders, such as non-alcoholic fatty liver disease (NAFLD). The metabolic changes associated with obesity are grouped to define metabolic syndrome, which is one of the main causes of morbidity and mortality in industrialized countries. NAFLD is considered to be the hepatic manifestation of metabolic syndrome and is one of the most prevalent liver diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 123 publications
1
54
0
Order By: Relevance
“…It has been suggested that OEA modulates food intake by increasing feeding latency, promoting control of energy intake, decreasing meal size, and increasing the intervals between meals by boosting the expression of genes associated with satiety . The major action of OEA in regulating food intake is mediated by PPAR‐α activation, an important transcriptional regulator of energy balance and fat metabolism . OEA is considered to be a high‐affinity PPAR‐α agonist .…”
Section: Major Mechanisms Of Action Of Oea In the Management Of Nafldmentioning
confidence: 99%
“…It has been suggested that OEA modulates food intake by increasing feeding latency, promoting control of energy intake, decreasing meal size, and increasing the intervals between meals by boosting the expression of genes associated with satiety . The major action of OEA in regulating food intake is mediated by PPAR‐α activation, an important transcriptional regulator of energy balance and fat metabolism . OEA is considered to be a high‐affinity PPAR‐α agonist .…”
Section: Major Mechanisms Of Action Of Oea In the Management Of Nafldmentioning
confidence: 99%
“…Pparg encodes the peroxisome‐proliferator‐activated receptor that is involved in the transcriptional regulation of lipid metabolism 37 and has been defined as a steatogenic factor 38 . Fabp2 and Cd36 encode membrane‐associated fatty acid‐binding proteins (fatty acid transporters) that facilitate and regulate cellular fatty acid uptake, 39 whereas Mogat1 is involved in an alternative pathway for triglyceride synthesis contributing to the development of hepatic steatosis, especially obesity‐related steatosis 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…PPARα activation induces the increase in fatty acid oxidation, ketogenesis and gluconeogenesis [32]. PPARβ/δ activation exerts regulatory effects on fatty acid catabolism, reverse cholesterol transport and energy metabolism, and even reduces insulin resistance and plasma glucose [33]. PPARγ shifts lipids from non-adipose organs such as the liver and skeletal muscles to white adipose tissue, leading to the attenuation of lipotoxicity [34].…”
Section: Discussionmentioning
confidence: 99%